The Anomalous Low State of the X-ray Binary System Hercules X-1 - Jurua, Edward (Doctoral dissertation, University of the Free State, 2008)
The light curve of Hercules X-1 (Her X-1) shows a peculiar 35-day modulation of the X-ray flux cycling between low and high states. The 35-day modulation is believed to result from the occultation of the neutron star by a warped processing disc around the central neutron star. Since the discovery of the 35-day cycle of Her X-1, it has entered the anomalous low state a number of times, with the most recent being during the 2003 - 2004 period. Using RXTE ASM observations of Her X-1 after the 2003 - 2004 anomalous low state, it is shown that Her X-1 turned on with a new precession period and main-on flux. It is further shown that there is a positive correlation between the precession period and the main-on flux. Using optical observations of Her X-1 during both the anomalous low state and the normal high state it is shown that the orbital (1.7 day) light curve of Her X-1 varies systematically over the 35-day precession cycle. It is also shown that there is insignificant change in the 35-day morphology of the light curves between the anomalous low state and normal high state of Her X-1, suggesting a very slight change in the disc warp between the two states. Comparison of optical and X-ray light curves suggest that the significant amount of X-ray flux during the anomalous low state originates from the companion star. Analysis of both RXTE PCA and XMM-Newton observations of Her X-1 during the 2003 - 2004 anomalous low state, show that Her X-1 was brighter during this period compared to the normal high state brightness, and that there are two components of X-ray flux during the anomalous low state: reflection component from the companion star and coronal component from the accretion disc corona.
Keywords: Accretion:accretion discs; Binaries:eclipsing; Stars:individual (Hercules X-1); Stars:neutron; X-rays:stars; Instabilities